Efecto de las microalgas chaetoceros gracilis, tetraselmis sp. e isochrysis galbana sobre la reproducción y desarrollo naupliar en copépodos calanoideos marinos tropicales, acartia spp. - Cambefort Florez, Santiago (2009)
Copepods form the major part of the wild marine zooplankton and are highly desired in marine pisciculture due to their nutritional value and high development results that have been reported when used as live food for marine fish fry. However, its cultivation is not as simple as that of other traditional foods and has only been developed in few countries. The present study is conducted in conjunction with the Achotines Laboratory (Panama) with the purpose of evaluating the possibility to create continuous cultures of marine calanoid copepods from the genus Acartia and keep them as live stock feed for the cultivation of marine fish. The work focuses specifically on the feeding and reproduction of copepods. It is divided into three parts: the first describes the effects of different diets on the amount of eggs produced by adult copepods, the second evaluates the larval growth and survival of Acartia nauplii fed with different diets, and the third verifies the effectiveness of a well known static culture method proposed by the investigator Glenn R. Schipp from the Darwin Aquaculture Centre. The results of the study provide a good basis for future research on the cultivation of local marine copepods and for the development of marine pisciculture in Panama.